RENCANA PEMASANGAN DISTRIBUTED GENERATION PADA JARINGAN DISTRIBUSI SERTA PENGARUHNYA TERHADAP PROFIL TEGANGAN DAN RUGI-RUGI DAYA - Artawan, A. A. T. B.; Sukerayasa, I W.; Ariastina, W. G. (Jurnal SPEKTRUM, 2020)
Jatiluwih feeder is a primary 20 kV distribution network with a peak demand of 1.85 MW. The feeder has a radial configuration with a length of 120 kmc. The extended length of the feeder causes a high voltage drop and power loss. One strategy to reduce voltage drop and power loss is by the installation of distributed generation (DG). The energy resource of the DG usually adopts local available renewable energy resources, such as solar power and hydro power. This paper discusses voltage profile and power loss due to the installation of DG on the distribution network. The analysis covered survey of the available renewable energy resources and power flow simulation. Power flow simulation was carried out in two scenarios, before and after the installation of DG. The simulation results showed that during peak daytime load, DG installation is able to reduce maximum voltage drop by 2,08 %, and increases the voltage from 344,4 V to 352,7 V. Besides that, the installation of DG is able to reduce the total power loss by 9,43 % or as much as 530 kW.